An Economical Half-Cell and Modified Rotating Disk Electrode for Electrochemical Characterizations of Fuel Cell Catalyst-Coated Membranes and Gas Diffusion Electrodes. (24th August 2017) - Bonakdarpour, Arman; Kwan, Jason; Pinaud, Blaise A; Daniel, Lius; Afonso, Greg; Wilkinson, David P
Abstract : We present a novel rotating disk electrode (RDE) tip and an economical half-cell approach for quick and precise measurements of oxygen reduction catalysts in forms of GDE and bonded GDE/membrane layers. In both cases repeatable and high quality cyclic voltammograms (CVs), oxygen reduction curves, and mass and specific activities for commercial CCMs were obtained in 0.1 M (RDE) and 1M (half-cell) HClO4 at room temperature (20°C). In both cases mass and specific activities are obtained and compared with fuel cell results. The activities determined are in agreement with those of the H2 /O2 fuel cell measurements under equivalent operating conditions.